Answer:
(a) 5
(b) 10
(c) 13
Step-by-step explanation:
We know the distance between two points is:
d=[tex]\sqrt{(x_{2} -x_{1} )^{2} +(y_{2}-y_{1})^{2}}[/tex]
we have the following pairs of points:
(a) (2, 4) and (5, 0)
[tex]d=\sqrt{(5 -2)^{2} +(0-4)^{2}} \\\\d=\sqrt{(3)^{2} +(-4)^{2}} \\\\d=\sqrt{9+16}\\\\d=\sqrt{25} = 5[/tex]
(b) (8, 1) and (2, -7)
[tex]d=\sqrt{(2 -8)^{2} +(-7-1)^{2}} \\\\d=\sqrt{(-6)^{2} +(-8)^{2}} \\\\d=\sqrt{36+64}\\\\d=\sqrt{100} = 10[/tex]
(c) (-4, 6) and (1,-6)
[tex]d=\sqrt{(1 -(-4))^{2} +(-6-6)^{2}} \\\\d=\sqrt{(5)^{2} +(-12)^{2}} \\\\d=\sqrt{25+144}\\\\d=\sqrt{169} = 13[/tex]